PEMETAAN VITALITAS BAHASA LAMPUNG DI WILAYAH PERKOTAAN LAMPUNG UTARA: UPAYA MENGHADAPI PERGESERAN PENGGUNAAN BAHASA IBU - Rachmatia, Meutia; Iqbal, Muhammad Galib; Masitoh, Masitoh; Putra, Kristian Adi; Fauziah, Abdillah Rizqy (Universitas Lampung, 2024)
This study examines the vitality of the Lampung language in urban areas of North Lampung, addressing the ongoing phenomenon of mother tongue language shift. Employing an ethnolinguistic framework with a combination of quantitative and qualitative methodologies, the research engaged 200 respondents across two age groups (15–30 years and >30 years) from three regions: Kotabumi, South Kotabumi, and North Kotabumi. Data collection was conducted via questionnaires, with analysis guided by UNESCO's language vitality parameters and results visualized using the ArcGIS application. Findings indicate that the Lampung language holds a